Peningkatan Kualitas Layanan Sertifikasi Halal Menggunakan Value Stream Mapping (VSM): IMPROVING THE QUALITY OF HALAL CERTIFICATION SERVICES USING VALUE STREAM MAPPING (VSM)) - A Shalihin (YCMM, 2022)
Halal customers want services that can bring their own satisfaction so that customers can return to using these services. Basically, customer satisfaction lies in the quality of service. Lean service is used for an approach that makes a service system optimal and effective. Problems in the service process that occur in halal certification services. In the halal certification process, there is still a waste of time which causes long queue waiting times. The concept of working to reduce the waste of waiting time is the lean service method. The tools used to solve problems using value stream mapping. In this study, the waiting time for the value stream mapping current state was 36537 minutes, while the value stream mapping future state processing time was 9980 minutes. There is a time reduction of 56.56%.